2006
DOI: 10.1128/jb.00869-06
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Population Analyses of a Recombination Event in the Catabolic Plasmid pJP4

Abstract: Cupriavidus necator JMP134(pJP4) harbors a catabolic plasmid, pJP4, which confers the ability to grow on chloroaromatic compounds. Repeated growth on 3-chlorobenzoate (3-CB) results in selection of a recombinant strain, which degrades 3-CB better but no longer grows on 2,4-dichlorophenoxyacetate (2,4-D). We have previously proposed that this phenotype is due to a double homologous recombination event between inverted repeats of the multicopies of this plasmid within the cell. One recombinant form of this plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Both genomic regions are flanked by IS 1071 elements. Such organization represents a composite transposon structure and in few cases actual transposition of such a structure was shown (Larrain‐Linton et al ., ; Ng and Wyndham, ). The association of both linuron catabolic gene clusters with IS 1071 supports the previous appraisal that the linuron catabolic pathway in WDL1 has resulted from patchwork assembly of catabolic gene modules allowing strain WDL1 to use linuron as the sole source of carbon and energy (Bers et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Both genomic regions are flanked by IS 1071 elements. Such organization represents a composite transposon structure and in few cases actual transposition of such a structure was shown (Larrain‐Linton et al ., ; Ng and Wyndham, ). The association of both linuron catabolic gene clusters with IS 1071 supports the previous appraisal that the linuron catabolic pathway in WDL1 has resulted from patchwork assembly of catabolic gene modules allowing strain WDL1 to use linuron as the sole source of carbon and energy (Bers et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative sequence analysis revealed that similar plasmid backbones carry various different degradative genes (Dennis, ). Experimental evidence and sequence data suggest that transposition, homologous and illegitimate recombination, gene duplication, and inversion must have contributed to the evolution of the catabolic genes present in the different plasmids analyzed so far (Dennis & Zylstra, ; Dennis, ; Larraín‐Linton et al ., ). The IncP‐9 plasmid pDTG1 has a remarkably different G+C content for genes encoding the upper pathway for the degradation of naphthalene to salicylate (52.7%) and those coding for the lower degradation pathway (61%), strongly suggesting that at least the genes coding for the upper degradation pathway originated from other organisms than Pseudomonads (Dennis & Zylstra, ).…”
Section: Successful Colonization Of Niches and Adaptation To Changingmentioning
confidence: 97%
“…Genetic modules which are frequently transferred in terrestrial environments via LGT are those allowing adaptation to rapidly evolving biotic interactions. These include antibiotic resistance genes [61] and degradative genes and pathways in response to the release of xenobiotics or new secondary metabolites [62,63]. Certainly, there is evidence that introduced microorganisms have the capacity to accelerate the degradation of contaminating hydrocarbons in Antarctic soils [64].…”
Section: Residual Biological Signals and Opportunities For Lateral Gene Transfermentioning
confidence: 99%